Framework to Enhance the Successful of Time Management in Construction Project - Ishak, Effa Affiana (Universiti Teknologi PETRONAS, 2018)
Construction industry in Malaysia benefits in the economically worth towards the development of the country, including providing the citizens and societies with a better infrastructure, transportation development and facilities for their comfort. Besides of these advantages, the negative impact caused by this industry can affect a lot of parties especially the company involved, government and also the societies. One of the major problems in this construction industry is time overrun and cost overrun which leads to bankruptcy, lost of profits, project abandonment and also society problems. Therefore, this study evaluates the factors affecting the delays of construction project through the application of structured questionnaire and case study of the high-rise construction project. The statistical techniques used to analyze the data gathered are Relative Importance Index (RII) and Average Index (AVI), while Cronbach’s alpha is used to measure the correlation between two different groups of respondents, the reliability and validity of the study.